Physical-mechanical properties and thermogravimetric analysis of fired clay brick incorporating palm kernel shell for alternative raw materials - Sarani, Noor Amira; Abdul Kadir, Aeslina; Md Din, Mohd Fadhil; Hashim, Azini Amiza; Hassan, Mohd Ikhmal Haqeem; Abdul Hamid, Nur Jannah; Huda Hashar, Nurul Nabila; Hissham, Nur Fatin Nabila; S.M. Johan, Siti Farhanah (Elsevier, 2023)
This article explores the potential of incorporating palm kernel shells (PKS) from palm oil mill waste as a clay replacement for fired clay bricks. PKS, an abundant byproduct of palm oil extraction, have high cellulose content and high calorific value, making them an ideal option for clay replacement in brick making. For this purpose, clay soil was replaced with different percentages of PKS (0, 1, 5 and 10%) and subjected to a firing temperature of 1050 ◦C (heating rate of 1 ◦C/min). The physical–mechanical properties such as shape, size, colour, dry density, water absorption, thermal conductivity, porosity and compressive strength, as well as microstructural and morphological properties (XRD, SEM-EDX and digital image) and thermal analysis data (TGA-DTA) were evaluated to determine the effects of replacing PKS in fired clay bricks. The results showed that the incorporation of PKS increased firing shrinkage and porosity and decreased dry density, compressive strength, and thermal conductivity. However, incorporating more than 5% PKS resulted in lower mechanical properties (24.6 to 11.0 MPa) and higher water absorption (3 to 12%) due to increased firing shrinkage and porosity (0.3 to 0.9% and 13 to 20%, respectively). The bricks also exhibited lower density (1799 to 1645 kg/m3 ) and improved thermal properties (0.54 to 0.36 W/m.K) due to the development of porosity during the firing process. While the degradation of organic components was a concern, it was determined that all organic components were completely degraded below 650 ◦C and the bricks matured at 950 ◦C. The study concluded that the use of PKS as a partial replacement for clay in brick manufacture is a viable solution for waste management.